Understanding heterogeneous preference of tourists for big game species: implications for conservation and management. (18th September 2012) - Di Minin, E.; Fraser, I.; Slotow, R.; MacMillan, D. C.
<x xml:space="preserve">Abstract</x> Read the Commentaries on this Feature Paper: To use tourism as a conservation tool, first study tourists; The Big 5 and conservation Response from the authors: Conservation marketing and education for less charismatic biodiversity and conservation businesses for sustainable development